Data Communications to Trains From High-Altitude Platforms - White, G.P.; Zakharov, Y.V. (IEEE transactions on vehicular technology, 2007)
The problem of providing simultaneous high data rate communication links to multiple moving railway trains from high-altitude platforms (HAPs) using a "smart" antenna array is addressed. Solutions are provided subject to system-level constraints: the number and position of interferers (trains), motion of both the trains and the HAP, and link budget for broadband transmission in the 31/28 GHz bands, assuming line-of-sight propagation. Techniques are studied for estimation of the number of trains present, accurate direction-of-arrival (DOA) estimation, and tracking of multiple trains for the purposes of beamforming (BF) and reliable attribution of DOA estimates to trains. A range of train scenarios, including trains crossing and passing through tunnels and shadowed stations, is considered. It is shown that extended Kalman filtering (EKF) applied to DOA estimates, in addition to providing improved accuracy of positional estimation of trains, also provides much more reliable attribution of DOA estimates to trains compared to DOA estimation alone - particularly when trains cross or pass closely. Methods for adapting EKF for tracking trains passing through tunnels and shadowed stations are proposed, and it is shown that tracking can be initialized to cope with both slow variations in train velocity and sudden HAP motion. BF that is based on null steering is shown to be beneficial in HAP-train data communications, even for small number of trains, providing increased stability of signal-to-interference-plus-noise ratio. Based on the analysis, array signal processing techniques are proposed based on an iterative root-MUSIC DOA method, extended Kalman tracking, and Capon BF.